Fabry Disease, a Rare Disorder with Cardiac Manifestations. The Problem of Diagnosis and Treatment: a Literature Review - Rudenko, Kostiantyn V.; Nevmerzhytska, Lidiia O.; Unitska, Olha M.; Danchenko, Polina A.; Leiko, Nadiia S. (Ukrainian Journal of Cardiovascular Surgery, 2022)
Fabry disease (FD) is an X-linked lysosomal storage disease caused by a mutation in the gene encoding α-galactosidase A and leads to reduced activity or complete absence of this enzyme, which causes the accumulation of globotriaosylceramide (Gb3) and its deacylated form (lyso-Gb3) in cells of the whole body. FD can occur both with multisystem manifestations, including damage to the nervous system, kidneys, and skin, and can affect only the heart. Cardiac involvement is a major cause of poor quality of life and death in patients with FD and an underrecognized cause of heart failure with preserved ejection fraction and ventricular arrhythmias in men over 30 years of age and women over 40 years of age. Cardiac damage begins at an early age, progresses subclinically until the appearance of significant symptoms, and usually manifests as leftventricular hypertrophy, mimicking hypertrophic cardiomyopathy. After the introduction of enzyme replacement therapy, early recognition of FD and differential diagnosis with other causes of leftventricular hypertrophy have become crucial to limit the progression of the disease. Recent advances in the understanding of cardiac pathophysiology and imaging have improved diagnostic and therapeutic approaches to the cardiac manifestations of this pathology. Modern achievements in the study of cardiac manifestations of FD have made it possible to significantly improve diagnostic and therapeutic approaches, in particular, in relation to the identification of pathogenetic mechanisms of organ damage and early disruption of their function. A better understanding of secondary pathogenic pathways, such as myocardial inflammation, may influence future therapeutic strategies and timely diagnosis of FD. Delay in diagnosis and untimely initiation of treatment remain critical problems for many patients with FD, especially for patients with late-onset cardiovascular manifestations, in whom treatment effects may be more limited and ineffective. Cooperation between specialists in genetic diseases and cardiologists remains important to identify patients before the appearance of cardiac symptoms in order to obtain maximum therapeutic effects.